Construction of Clostridium tyrobutyricum strain and ionic membrane technology combination pattern for refinery final molasses recovery and butyric acid production - Wang, Bing; Zhou, Xiang; Liu, Wei; Liu, Mei-Han; Mo, Dan; Wu, Qing-Feng; Wang, Ya-Juan; Zhang, Miao-Miao; Chen, Lei; Yuan, Shan; Zhou, Bo; Li, Xin; et al. (Frontiers in Microbiology, 2023)
Introduction Clostridium tyrobutyricum has considerable prospect in the production of organic acids. Globally, refinery final molasses is rich in sugar and reported to have high levels of accumulation and high emission costs, recognized as an excellent substrate for C. tyrobutyricum fermentation, but there is no suitable method available at present. Methods In this study, an acid-base treatment combined with a new green membrane treatment technology – a dynamic ion-exchange membrane -was used to pretreat refinery final molasses, so that it could be used for C. tyrobutyricum to produce butyric acid. A high-performance liquid chromatography method was established to determine the conversion of a large amount of sucrose into fermentable sugars (71.88 g/L glucose and 38.06 g/L fructose) in the treated refinery final molasses. The process of sequential filtration with 3, 1, and 0.45 μm-pore diameter dynamic ion-exchange membranes could remove impurities, pigments, and harmful substances from the refinery final molasses, and retain the fermentable sugar. Results and discussion This means that refinery final molasses from the sugar industry could be utilized as a high-value by-product and used for the growth of C. tyrobutyricum, with industrial feasibility and economic competitiveness. Using the treated refinery final molasses as a carbon source, C. tyrobutyricum was screened by the method of adaptive evolution. The strain with butyric acid yielded 52.54 g/L, and the yield of the six carbon sugar was increased from 0.240 to 0.478 g/g. The results showed that combination of C. tyrobutyricum and ionic membrane technology broke through the bottleneck of its utilization of refinery final molasses. This study provided an innovative idea for the C. tyrobutyricum fermentation to produce butyric acid.